2001
DOI: 10.1086/320546
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Integral Field Spectroscopy and Mid‐Infrared Spectroscopy of the Starburst Galaxy M82

Abstract: We present new infrared observations of the central regions of the starburst galaxy M 82. The observations consist of near-infrared integral field spectroscopy in the H-and K-band obtained with the MPE 3D instrument, and of λ = 2.4 − 45 µm spectroscopy from the Short Wavelength Spectrometer (SWS) on board the Infrared Space Observatory. These measurements are used, together with data from the literature, to (1) re-examine the controversial issue of extinction, (2) determine the physical conditions of the inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(41 citation statements)
references
References 124 publications
4
35
2
Order By: Relevance
“…A.2 and A.3 the observed spectral energy distributions of our sample sources with the empirical SED of M 82 scaled to fit the measured LW3 flux (thick continuous line). The M 82 SED has been taken partly from Silva et al (1998), partly from the observed ISOCAM-CVF low-resolution spectrum between 5 and 18 µm by Foerster-Schreiber et al (2001), in order to get a proper representation of the PAH spectrum which is critical for interpreting the LW3 fluxes. In the Elbaz's et al analysis We report in Fig.…”
Section: Estimating the Rate Of Ongoing Star Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…A.2 and A.3 the observed spectral energy distributions of our sample sources with the empirical SED of M 82 scaled to fit the measured LW3 flux (thick continuous line). The M 82 SED has been taken partly from Silva et al (1998), partly from the observed ISOCAM-CVF low-resolution spectrum between 5 and 18 µm by Foerster-Schreiber et al (2001), in order to get a proper representation of the PAH spectrum which is critical for interpreting the LW3 fluxes. In the Elbaz's et al analysis We report in Fig.…”
Section: Estimating the Rate Of Ongoing Star Formationmentioning
confidence: 99%
“…However, dusty starbursts show occasional evidence in the starburst regions for the presence of younger red supergiants as shown by the pronounced [CO] 2.3 µm absorption (e.g. Foerster-Schreiber et al 2001). Obviously, a contribution by such young massive stars, even heavily extinguished, would substantially decrease the M/L in the near-IR, hence affecting the stellar mass estimate.…”
Section: Estimating the Baryonic Massesmentioning
confidence: 99%
“…4.4.1. See also discussion in Förster-Schreiber et al 2001). For all three elements, the major ionisation stages found in H II regions are covered by the ISO-SWS spectra, which minimises the required ionisation correction factors.…”
Section: Introductionmentioning
confidence: 99%
“…The high ISM pressure is supplied by hot gas (kT ∼ 0.7-0.9kev) that pervades the region around the main starburst clumps. The structure of the ISM in M82 thus is quite different from that in the Milky Way's disk (see also Förster-Schreiber et al 2001, 2003.…”
Section: Cymcs and Starburst Clumps In M82mentioning
confidence: 99%
“…Taking full advantage of the opportunities opened by AO on ELTs in the near infrared will require continued preparatory work on infrared properties of stellar populations covering a range in age. Much of the necessary data can be obtained in the Local Group using existing telescopes, providing an excellent starting point for spectroscopic surveys of key infrared spectroscopic characteristics of SSPs and composite stellar populations (Förster-Schreiber et al 2001, 2003.…”
Section: Opportunities For Extremely Large Telescopesmentioning
confidence: 99%